Cofilin-1 Is a Mechanosensitive Regulator of Transcription - Domingues, Catarina; Geraldo, A. Margarida; Anjo, Sandra Isabel; Matos, André; Almeida, Cláudio; Caramelo, Inês; Lopes-da-Silva, José A.; Paiva, Artur; Carvalho, João; Pires das Neves, Ricardo; Manadas, Bruno; Grãos, Mário (Frontiers in Cell and Developmental Biology, 2020)
The mechanical properties of the extracellular environment are interrogated by cells and integrated through mechanotransduction. Many cellular processes depend on actomyosin-dependent contractility, which is influenced by the microenvironment’s stiffness. Here, we explored the influence of substrate stiffness on the proteome of proliferating undifferentiated human umbilical cord-matrix mesenchymal stem/stromal cells. The relative abundance of several proteins changed significantly by expanding cells on soft ( 3 kPa) or stiff substrates (GPa). Many such proteins are associated with the regulation of the actin cytoskeleton, a major player of mechanotransduction and cell physiology in response to mechanical cues. Specifically, Cofilin-1 levels were elevated in cells cultured on soft comparing with stiff substrates. Furthermore, Cofilin-1 was de-phosphorylated (active) and present in the nuclei of cells kept on soft substrates, in contrast with phosphorylated (inactive) and widespread distribution in cells on stiff. Soft substrates promoted Cofilin-1-dependent increased RNA transcription and faster RNA polymerase II-mediated transcription elongation. Cofilin-1 is part of a novel mechanism linking mechanotransduction and transcription.